Modal analysis of concrete bridge decks subjected to free vibration / Norshariza Mohamad Bhkari, Azlan Abd Rahman and Baderul Hisham Ahmad - Mohamad Bhkari, Norshariza; Abd Rahman, Azlan; Ahmad, Baderul Hisham (Universiti Teknologi MARA Cawangan Pahang, 2006)
This paper reports a study on free vibration dynamic analysis for determining vibration parameters such as natural frequencies and mode shapes for two selected bridges in Johor. The vibration parameters for these bridges are studied using finite element analysis software package ANSYS 6.0. A three- imensional finite element model is developed for the bridges based on design drawing provided by the Public Works Department (PWD). Separate element types with same nodal layer are used as a modeling technique in this finite element analysis. Mode shapes based on natural frequency analysis are obtained for the bridges from the models with and without diaphragms. It is found that a moderately coarse mesh density of 1m for every edge element length would be sufficient for a majority of practical structural applications.